Quaderni di traduzioni (1929-1932) [Translation Notebooks (1929-1932)], 2 vols, Giuseppe Cospito and Gianni Francioni (eds) (in English) - Wagner, Birgit (International Gramsci Journal, 2023)
Before Gramsci was given permission to write what we now know as his Quaderni del carcere (Prison Notebooks), he filled four other notebooks with translations (mainly from German, but also from Russian and some exercises from English); he also then included some translations from Marx in Notebook 7 in particular. In the translation notebooks we see him as an “apprentice translator”, certainly, but also note his overall approach to problems that are the constant preoccupation of translation scholars, his translations of the collection of folk tales collected by the Brothers Grimm being a case in point. Among other texts translated are a volume on historical linguistics and the 1927 number of “Die literarische Welt” on the new school of American social fiction, exemplifying the growing strata of United States intellectuals. The nineteenth-century Russian classics also aroused his interest for their link with and input into social ferment that was then beginning to grow in that country. Thus the link with some of the themes and subjects of what all regard as his major work and interests emerges clearly in these hitherto rather neglected notebooks.